Littoral Slope, Water Depth and Alternative Response Strategies to Light Attenuation Shape the Distribution of Submerged Macrophytes in a Mesotrophic Lake - He, Liang; Zhu, Tianshun; Wu, Yao; Li, Wei; Zhang, Huan; Zhang, Xiaolin; Cao, Te; Ni, Leyi; Hilt, Sabine (Frontiers in Plant Science, 2019)
Light is a major limiting resource in aquatic ecosystems and numerous studies have investigated the response of submerged macrophytes to low light conditions. However, few studies have tested whether different light response strategies can also have consequences for macrophyte distribution along different littoral slopes in lakes, which are known to affect macrophyte biomass due to differences in drag forces and sediment characteristic. In this study, we tested 1) whether two macrophyte species of different growth forms (canopy-forming: Potamogeton maackianus, rosette-type: Vallisneria natans) differ in their response strategies to low light conditions and 2) how these responses influence their distribution along different basin slopes in the mesotrophic Lake Erhai, China. We hypothesized that the canopy-forming species responds to low light conditions at deeper sites by stem elongation while the rosette-type species increases its shoot chlorophyll content. As a consequence, P. maackianus should have a higher susceptibility to drag forces and thus prevail at sites with lower slopes. Sites with higher slopes should offer a niche for rosette-type species like V. natans that can better withstand drag forces. We surveyed the distribution and abundance of the two macrophyte species at 527 sampling points along 97 transects in Lake Erhai and measured their height, leaf and stem/rhizome biomass, and leaf chlorophyll a content at different water depths. Our results confirmed stem elongation as a strategy to low light conditions by the canopy-forming species P. maackianus, while V. natans produced more chlorophyll a per shoot biomass at deeper sites to tolerate shading. As hypothesized, these alternative response strategies to low light conditions resulted in a trade-off regarding the plants ability to grow at different basin slopes. P. maackianus was dominant at sites with low-moderate slope (0-4%) and low-moderate water depth (2-4 m), while sites with high basin slope (4-7%) combined with moderate-high water depth (3-5 m) were predominantly colonized by V. natans. The latter habitat thus represents a potential refuge for rosette-type macrophyte species that are often outcompeted when shading increases during eutrophication.